ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF MEDICAL LECTURERS CASE STUDY AT PRIVATE “X” UNIVERSITY INDONESIA - William William; Kholil Kholil; Tatan Sukwika; Nafiah Ariyani (Dinasti International Journal of Management Science, 2022)
Indonesia launched a program to improve the quality of human resources (HR) as a driving factor for competitiveness. Universities have an important role in producing quality human resources and for this to occur, good lecturer performance is also needed. In fact, the performance of human resources educators in Indonesia has not been as expected. Performance is the result of work both in quantity, quality, and the influence is multifactorial. Therefore, this research aims to obtain these factors, so that it can help educational institutions, especially medical study programs, in taking policies that can improve lecturer performance. This research was conducted by interviewing 20 medical lecturers with three stages, namely the first stage: identification of variables, the second stage: identification of variable relationships and the third stage of analysis of the results of the first and second stages with MICMAC analysis. There are 22 variables that affect the performance of medical lecturers and divided into independent variables, dependent variables, linkage variables, and autonomous variables. The variables that have the most direct influence on other variables are leadership, commitment and credit point. The variables that are strongly influenced indirectly are motivation, namely by credit point, and commitment. The linkage variables that strongly problematic for direct relationships are internal regulations, leadership, ability, work environment and workload; and for indirect relationship is commitment. It can be concluded that the variables that affect the performance of medical lecturers are numerous, and the relationship is very complex between one variable to another.